Crystal structure of N-(4-bromophenyl)-4-[3-(trifluoromethyl)phenyl]-piperazine1-carbothioamide, C18H17BrF3N3S - Al-Sanea, Mohammad M.; Blacque, Olivier; Mohamed, Ahmed A. B.; Tiekink, Edward R. T. *; El-Eman, Ali A. (De Gruyter, 2023)
C18H17BrF3N3S, triclinic, P1 (no. 2), a = 8.6380(2) Å, b = 14.5082(3) Å, c = 14.8000(3) Å, α = 98.177(2)°, β = 97.015(2)°, γ = 91.111(2)°, V= 1820.89(7) Å3 ,Z = 4,Rgt(F) = 0.0296,wRref(F2) = 0.0783, T= 160 K. CCDC no.: 2221199